Thrombophilia in Pediatric Patients with Multisystem Inflammatory Syndrome in Children Secondary to Coronavirus Disease 2019 Supported on Extracorporeal Membrane Oxygenation. Issue 1 (January 2021) - Minen, Federico; Hands, Christopher; Mustafa, Muhammad R; Pienaar, Alison; Lillie, Jon
Abstract : Coronavirus disease 2019 (COVID-19) in adults has been associated with thrombosis. Multisystem inflammatory syndrome in children (MIS-C) with COVID-19 case series have reported high fibrinogen levels, but it is not known whether this causes thrombophilia. We report two patients needing extracorporeal membrane oxygenation (ECMO) who both suffered thrombotic complications. We retrospectively reviewed patients with MIS-C needing ECMO support admitted to a single Paediatric and Cardiac Intensive Care Unit within a regional center for MIS-C in South East England. Two children required ECMO for cardiovascular support. Both developed thrombotic events despite receiving heparin infusions at dosing higher than the interquartile range for our ECMO population. Case 1 developed a right anterior and middle cerebral artery infarct, which led to his death. Case 2 had a right atrial thrombus, which resolved without complication. When compared with patients undergoing ECMO in the same institution in pre-MIS-C era, fibrinogen levels were consistently higher before and during ECMO therapy. MIS-C patients presenting with hyperfibrinogenemia are likely to have a propensity toward thrombotic complications; this must be considered when optimizing the anticoagulation strategy on ECMO. Abstract : Supplemental Digital Content is available in the text.